Nursing Profession in Times of War and Humanity: Insights from Siti Rufaidah's Legacy - Henri Setiawan; Suhanda Suhanda (Inspirasi Foundation, 2023)
In armed conflicts, innocent people are often the victims of violence and brutality. War not only destroys infrastructure and the environment, but also destroys human morals and ethics. However, there are several humanitarian principles that must be upheld. These principles are set out in the Geneva Conventions and Additional Protocols, which form the basis of international humanitarian law. However, in reality there are still many countries that violate these principles. Violence and abuse against civilians, prisoners of war, and the injured continue to occur in many conflicts around the world. Nurse is a health profession that has an important role in war. They work on the front lines to provide medical care to victims of conflict, including military troops, prisoners of war, and civilians injured or sick as a result of the conflict. Nurses performed a variety of tasks during war, including treating patients with gun wounds, preparing medical equipment, taking blood samples for diagnosis, and providing psychological assistance to patients traumatized by the conflict. In the history of Islam and world civilization, many wars occurred during the time of the Prophet Muhammad (PBUH). Siti Rufaidah was one of the well-known nurse figures at that time and was often present in providing medical assistance to war victims. One of the proofs of her patentability in the world of nursing is during the Khandaq war. Siti Rufaidah at that time treated Sa'ad bin Muadz who was injured by an arrow until his condition stabilized and improved. The presence of Siti Rufaidah has had a huge impact on the development of the nursing profession in the Islamic world, and even today. She is a role model for Muslim nurses around the world.